2018
DOI: 10.1001/jamacardio.2018.2866
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetically Enhanced Lipoprotein Lipase–Mediated Lipolysis and Low-Density Lipoprotein Cholesterol–Lowering Alleles With Risk of Coronary Disease and Type 2 Diabetes

Abstract: Key PointsQuestionAre genetically determined differences in lipoprotein lipase (LPL)–mediated lipolysis and low-density lipoprotein cholesterol (LDL-C)–lowering pathways independently associated with risk of coronary disease and diabetes?FindingsIn this genetic association study including 392 220 people, triglyceride-lowering alleles in LPL or its inhibitor ANGPTL4 were associated with lower risk of coronary artery disease and type 2 diabetes in a consistent fashion across quantiles of the population distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 59 publications
7
58
0
2
Order By: Relevance
“…In a large cross-sectional study by Khera et al, they found that the presence of rare damaging mutations in the lipoprotein lipase gene (LPL) was substantially associated with higher levels of TGs and a diagnosis of IHD [78]. Similar results have been obtained by Lotta et al, who uncovered a relation between a polymorphism of the LPL gene and a lower risk of IHD among people carrying alleles corresponding to low TG levels in the blood, irrespective of genetic mechanisms lowering the level of low-density lipoprotein (LDL) cholesterol [79]. In international literature, rather frequently, there are descriptions of both isolated cases and of meta-analyses suggesting that low levels of LPL in serum are linked with early atherosclerosis (before 55 years of age), whereas a higher LPL activity has a protective effect against the development of IHD.…”
Section: Lipoportein Lipase (Lpl)supporting
confidence: 64%
“…In a large cross-sectional study by Khera et al, they found that the presence of rare damaging mutations in the lipoprotein lipase gene (LPL) was substantially associated with higher levels of TGs and a diagnosis of IHD [78]. Similar results have been obtained by Lotta et al, who uncovered a relation between a polymorphism of the LPL gene and a lower risk of IHD among people carrying alleles corresponding to low TG levels in the blood, irrespective of genetic mechanisms lowering the level of low-density lipoprotein (LDL) cholesterol [79]. In international literature, rather frequently, there are descriptions of both isolated cases and of meta-analyses suggesting that low levels of LPL in serum are linked with early atherosclerosis (before 55 years of age), whereas a higher LPL activity has a protective effect against the development of IHD.…”
Section: Lipoportein Lipase (Lpl)supporting
confidence: 64%
“…Previous reports have suggested that certain gene variants that lower TG concentrations and reduce CVD risk can also influence the risk of type 2 diabetes (15,(46)(47)(48)(49)(50). Previous studies have also implicated a relationship between ANGPTL3 levels and risk of type 2 diabetes (15,46).…”
mentioning
confidence: 99%
“…Biomarkers in Evaluation of Coronary Stenosis Биомаркеры в оценке коронарного стеноза С изучением роли новых биомаркеров в процессах атерогенеза связывается возможность дополнить современные представления относительно его молекулярных механизмов и биохимической природы формирования [1]. Если роль холестерина липопротеинов низкой плотности (ХС-ЛПНП) как фактора риска развития атеросклероза и ишемической болезни сердца (ИБС) убедительно доказана, то результаты исследований относительно триглицеридов (ТГ) и холестерина липопротеинов высокой плотности (ХС-ЛПВП) являются весьма противоречивыми [2]. В качестве одного из информативных визуальных маркеров атеросклероза рассматривается эхокардиографически измеренная толщина эпикардиальной жировой ткани (тЭЖТ) [3].…”
Section: Discussionunclassified
“…Мы полагаем, что именно такое сочетание факторов способно облегчить проникновение в интиму ТГ-обогащенных остаточных частиц и реализацию их проатерогенных эффектов [7,8]. Крайне важными в этой связи представляются данные полногеномных исследований, показавших, что воздействие на липопротеинассоциированную липазу -ключевой фермент, гидролизующий обогащенные ТГ частицы, может обеспечить дополнительное снижение кардиоваскулярного риска у пациентов, уже получающих ЛПНП-снижающую терапию [2]. Доказано, что снижение уровня ТГ крови на 35-50% и возрастание уровня ХС-ЛПВП на 5-20% под влиянием фенофибрата сопровождается уменьшением накопления висцеральной жировой ткани и содержания провоспалительных адипокинов, ограничением процессов воспаления, инсулинорезистентности и оксидативного стресса, что препятствует атерогенезу [8,9].…”
Section: Biomarkers In Evaluation Of Coronary Stenosisunclassified